2020
DOI: 10.1002/jeq2.20136
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency methane capture by living fungi and dried fungal hyphae (necromass)

Abstract: B i o r e m e d i a t i o n a n d B i o d e g r a d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…However, keystone species analysis showed that fungi, at the least, play a role equally as important as those of key chemolithoautotrophic bacteria and archaea. Previous studies on filamentous fungi showed that hydrophobins, a group of proteins on the surface of fungal hyphae, give them the ability to solubilize otherwise insoluble inorganic compounds such as methane and polycyclic aromatic molecules by increasing the partition coefficient, increasing their bioavailability by magnitudes ( 37 , 77 , 78 ). Previously, Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, keystone species analysis showed that fungi, at the least, play a role equally as important as those of key chemolithoautotrophic bacteria and archaea. Previous studies on filamentous fungi showed that hydrophobins, a group of proteins on the surface of fungal hyphae, give them the ability to solubilize otherwise insoluble inorganic compounds such as methane and polycyclic aromatic molecules by increasing the partition coefficient, increasing their bioavailability by magnitudes ( 37 , 77 , 78 ). Previously, Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%